Effects of Propeller Distribution on the Aeroelastic Characteristics of Large-Deformation Wings - Xuan Wu; Zhou Zhou; Zhengping Wang (Aerospace)
Considering the large-deformation and multi-propeller characteristics of very flexible aircraft, propeller effects are introduced and accessed in the wing static and dynamic aeroelastic analysis and different propeller distributions are utilized to obtain more aeroelastic benefits. The propeller–wing aeroelastic interactions are innovatively modeled in the paper. For propeller–wing aerodynamic interaction, propeller-induced velocities are considered and added in the nonplanar steady and unsteady vortex lattice methods. For propeller–wing structural interaction, the conversion of loads and displacements between attached propellers and the large-deformation wing is derived. Static aeroelastic cases indicate that thrust can reduce structural deformation and slipstream can cause considerable lift increment. Dynamic cases indicate that thrust can reduce the wing’s maximum response to gust and bring an improvement of 9.4% in the wing’s critical velocity, while slipstream can reduce the gust response amplitude. In addition, using smaller and more propellers is recommended instead of an individual larger propeller. Decreasing and increasing propeller speeds toward the wingtip is more beneficial for cruise status and gust alleviation, respectively.